Penguatan Pengelolaan Keuangan Desa Berbasis Kemitraan Melalui Pembuatan Web Desa Wujud Profil Desa Huangobotu - Ayu Rakhma Wuryandini; Annisiah Bito; Yuska Rahayu Djunaidi; Juwita Kanon; Felix Ferdinal Edy Thungasal; Elfin Elfin (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The purpose of this community service activity is to strengthen partnership-based village financial management in the Tomini Bay area. The problem that occurred in Huangobotu village, Kabila Bone sub-district, Bone Bolango district, Gorontalo province was that Huangobotu village did not yet have a village website to serve as a village profile, not just to introduce Huangobotu village to the public, but the expected goal was for Huangobotu village to become a fostered village that successfully published all activities related to the transparency of village financial management. The methods used in this study were 1) Coaching socializing material about the application to KKS supporting students, 2) Providing training on making the Village Web to KKS supporting students, 3) Assistance in training village web creation to village apparatus 4) Official Village Web Publication to the people of Huangobutu village. The results of the KKS program have been running smoothly, this is evidenced by the success of the servants in implementing the knowledge obtained at tertiary institutions to village apparatus with the Huangobotu village website and village apparatus being able to make the village website on an ongoing basis as a means of information for the public and as a village profile. Village Web, Strengthening Village Financial Management; Means